Significados e percepções do homem diante da gravidez de sua companheira com síndromes hipertensivas - Carvalho, Jovanka Bittencourt Leite de (2010)
The general aim of the research was to comprehend the Social Representations constructed by the man in the face of his companion s risk pregnancy caused by hypertensive syndromes. The study is of exploratory and descriptive character in a qualitative approach developed at two public maternity hospitals, both located in Natal-RN, with 65 men whose wives had undergone high-risk pregnancy. The project was submitted to the Ethics on Research Committee of the Federal University of Rio Grande do Norte, Brazil (CEP-UFRN), with favorable report no. 81/07. For data collection, the following multimethods were employed: a word free association test; a projective test for registering mental images; and a semistructured interview schedule. The speech contents were analyzed in accordance with the Theory of Social Representations and complemented by the Central Nucleus Theory. The discussion of the results was grounded on literary findings of the companion s participation in pregnancy as well as in risk pregnancy associated with hypertensive syndromes. The data showed fear as representation s central nucleus, while recollections of that feeling referred to death of both companion and child in addition to fear of the unknown. The categories preoccupation and carefulness, other feelings, and clinical picture of the disease represented components of the peripheral nucleus. The results concerning mental images followed the same category criteria of the word free association test fear, other feelings, preoccupation, carefulness, and clinical picture of the disease. After being processed in accordance with the principles of content analysis, the statements originated three thematic unities: fear and insecurity in the presence of the companion s risk pregnancy; attitudes of carefulness to the risk pregnancy of the partner; and humanized assistance during the companion s risk pregnancy. Considering the results, the conclusion is that the partner s risk pregnancy caused by hypertensive syndromes represents, for the man, feelings of fear, preoccupation, insecurity, lack of acceptance and information, as well as attitudes of carefulness. The results reveal necessity of reorganizing the obstetric assistance with an eye to including the man as participant in the reproductive process. That demands extension of humanized carefulness to the companion with a view to make him an active coadjutor in the assistance of high-risk pregnant